Réponses

2014-06-17T21:35:29+02:00
Δ = b² - 4ac
Δ = 50² - 4 x 4 x (-6)
Δ = 2596

x_1 =  \frac{-50 -  \sqrt{2596} }{8}


x_2 =  \frac{-50 +  \sqrt{2596} }{8}

Donc :

4 x^{2}  + 50x - 6 = 4(x -  \frac{-50 -  \sqrt{2596} }{8} )(x -  \frac{-50+ \sqrt{2596} }{8})


  • Utilisateur Brainly
2014-06-17T21:42:05+02:00


4x²+50x-6

Δ= b²-4ac = 50² -4 * 4 * (-6) = 2500 + 96 = 2596

Donc x1 = (-b-√Δ)/2a = (-50 - √2596)/ 2*4 = (-50 - √2596) / 8

et x2 = (-b+√Δ) / 2*a = (-50+√2596)/ 2*4 = (-50 - √2596) / 8

Donc la forme factorisée est 4(x -x1)*(x-x2)